Different Processed Products of Curcumae Radix Regulate Pain-Related Substances in a Rat Model of Qi Stagnation and Blood Stasis - Chen, Zhimin; Hu, Lin; Liao, Yujiao; Zhang, Xi; Yang, Zhuo; Hu, Changjiang; Yu, Lingying (Frontiers in Pharmacology, 2020)
Background: Curcumae Radix (Yujin) has been widely used to treat Qi stagnation and blood stasis in TCM. The tuberous roots of Curcuma longed L. (i.e. Huangsiyujin, HSYJ) is one of the major species of Yujin based on the Chinese Pharmacopoeia. According to the processing theory of TCM, Yujin stir-frying with vinegar might strengthen the effect of dispersing stagnated hepatoqi to relieve pain and stir-frying with wine might strengthen the effect of promoting blood circulation for removing blood stasis. However, the mechanism for the enhancement of clinical efficacy by processing is unclear. Aim/Hypothesis: This study was aimed at evaluating the effect of different processed products of HSYJ on chemical constituents and pain related substances, to explore underlying mechanisms of HSYJ in treating pain caused by Qi stagnation and blood stasis. Methods: The effects of different processing methods on the paste yield of water decoction were analyzed, and the content of main constituents were detected by HPLC. Rat model of Qi stagnation and blood stasis was established by tail clamp stimulation combined with adrenaline subcutaneous injection. After treatment and intervention with HSYJ and its processed products, β-endorphin (β-EP) and 5-hydroxytryptamine (5-HT) were measured by ELISA, expression of c-fos was evaluated by immunohistochemistry. Results: After stir-fring with vinegar or wine, the extract yield and curcumins content increased. Compared with model group, raw HSYJ could significantly improve the abnormality of 5-HT in plasma (P < 0.05) and β-EP in brain (P < 0.01). Stir-frying HSYJ with vinegar or wine could significantly improve the abnormality of 5-HT in plasma, β-EP in brain and the expression of c-fos (P < 0.01). Stir-frying HSYJ with vinegar could also significantly increase the level of β-EP in plasma (P < 0.05). Conclusions: These results showed that different processing methods have certain effects on the chemical constituents of HSYJ, mainly in increasing the decoction rate and curcumins content. HSYJ and its processed products can reduce 5-HT level, increase β-EP level and inhibit the expression of c-fos in model rats. The effects of stir-fring HSYJ with vinegar on β-EP level in plasma was superior to others.